THE BRAZILIAN DISTRIBUTIVE CONFLICT IN THE EARLY 21ST CENTURY AND THE ROLE OF THE FOREIGN SECTOR - Santoro, João P. C.; N. Rolim, Lilian (Investigación Económica, 2023)
The first two decades of the 21st century in Brazil were characterized by an increase in the wage share, which was largely associated with the higher workers’ bargaining power that resulted from institutional changes and lower unemployment. We show that the foreign sector also played a key role in this process and explore how its effects on the domestic income distribution changed over the years. We highlight the importance of the industry and, in particular, the manufacturing sector to the higher wage share. At the beginning of the period the depreciated domestic currency did not compromise the profit share due to the low bargaining power of workers, while during the years of appreciated domestic currency the distributive conflict was attenuated. Yet, the currency depreciation after 2011 occurred in an economic structure more dependent on imports and with high workers’ bargaining power, thus pressuring downwards profit margins. EL CONFLICTO DISTRIBUTIVO BRASILEÑO A PRINCIPIOS DEL SIGLO XXI Y EL PAPEL DEL SECTOR EXTERIOR RESUMEN Las dos primeras décadas del siglo XXI en Brasil se caracterizaron por un aumento de la participación salarial, que estuvo asociado en gran medida al mayor poder de negociación de los trabajadores resultante de los cambios institucionales y de la reducción del desempleo. Mostramos que el sector extranjero también desempeñó un papel clave en este proceso y exploramos cómo cambiaron sus efectos sobre la distribución del ingreso interno a lo largo de los años. Destacamos la importancia de la industria y, en particular, del sector manufacturero en la mayor participación salarial. En el inicio del periodo la moneda nacional depreciada no comprometió la participación de los beneficios debido al bajo poder de negociación de los trabajadores, mientras que durante los años de moneda nacional apreciada el conflicto distributivo se atenuó. Sin embargo, la depreciación de la moneda después de 2011 se produjo en una estructura económica más dependiente de las importaciones y con un alto poder de negociación de los trabajadores, presionando a la baja los márgenes de beneficio.